(untitled) (Euro-Latin American Journal of Administrative Law, 2014)
This article aims to analyse the issue of State liability for environmental damage, seeking to identify their requirements and configuration assumptions in the light of the Brazilian Constitution of 1988 and the legal provisions related to the theme.